Psychological Distress, Japanese Teleworkers, and Supervisor Support During COVID-19. Issue 2 (17th February 2023) - Kikunaga, Kazuki; Nakata, Akinori; Kuwamura, Mami; Odagami, Kiminori; Mafune, Kosuke; Ando, Hajime; Muramatsu, Keiji; Tateishi, Seiichiro; Fujino, Yoshihisa; ,
Abstract : This study underlines workplace social support's significance for teleworkers' mental health in Japan during the COVID-19 pandemic. Notably, employees' job positions and teleworking situation were found to impact the associations between workplace social support and psychological distress. Hence, inadequate supervisor support may be a risk factor for teleworkers' psychological distress. Abstract : Objective: During the COVID-19 pandemic, teleworking became the new workplace norm, creating a new challenge for workplace communication. This study investigated the association between source-specific workplace social support and psychological distress among Japanese teleworkers and nonteleworkers. Methods: A total of 15, 045 workers were extracted from a cross-sectional web-based survey that assessed psychological distress, workplace social support from supervisors and coworkers. After grouping participants into four groups based on their positions (managers, staff members) and teleworking arrangements (teleworking, nonteleworking), multiple logistic regression analyses were performed separately. Results: Teleworkers with less supervisor support demonstrated the highest risk of psychological distress (adjusted odds ratio = 2.55, P = 0.024). Conclusions: Insufficient supervisor support for teleworking staff members may be a key occupational risk factor for psychological distress in the postpandemic future.